2012
DOI: 10.1021/jp301316e
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-Sensitized Photodegradation of Bilirubin and Potential Therapeutic Application

Abstract: Bilirubin (BR) is a protective antioxidant; however, when its conjugation and excretion are impaired, as in neonatal and hereditary jaundice, BR accumulates and may cause severe neurotoxicity. Here, we report a novel mechanism for ZnO nanoparticle (NP)-sensitized BR degradation via defect-mediated nonradiative energy transfer pathway. Among different sizes and shapes, ZnO particles with diameter of 5 nm having very high concentration of defect states are found to be the most effective catalyst, which particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 47 publications
1
23
0
Order By: Relevance
“…Hence, the photoproducts formed after the photocatalysis of BR in the presence of ZnO nanoparticles should mainly contain the structural ( Z -lumirubin) and configurational (( Z , E )-BR) isomers of water-insoluble BR, which are the usual photoproducts of the BR phototherapy [2]. In addition, the presence of methylvinylmaleimide (MVM) as an outcome of the photocatalytic degradation of BR in the presence of ZnO nanoparticles has also been evidenced in our previous study [15]. …”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Hence, the photoproducts formed after the photocatalysis of BR in the presence of ZnO nanoparticles should mainly contain the structural ( Z -lumirubin) and configurational (( Z , E )-BR) isomers of water-insoluble BR, which are the usual photoproducts of the BR phototherapy [2]. In addition, the presence of methylvinylmaleimide (MVM) as an outcome of the photocatalytic degradation of BR in the presence of ZnO nanoparticles has also been evidenced in our previous study [15]. …”
Section: Resultsmentioning
confidence: 84%
“…Using picosecond-resolved spectroscopy techniques we have recently demonstrated that both singly charged (V O + ) and doubly charged (V O ++ ) oxygen vacancy centers contribute to the energy transfer process with efficiencies of about 78% and 89%, respectively [15]. In the present study, the average lifetime (τ avg ) of the fluorescence decay of the as-synthesized ZnO nanoparticles was found to be reduced by an order of magnitude upon the addition of BR, from 8.78 ns to 0.79 ns, with an energy transfer efficiency ( E ) of 91.53%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 3 a shows a prototype photodevice for investigation of the photocatalytic efficiency of the nanohybrid under visible‐light irradiation. Full details of the device may be found in our earlier publication 26. The test water under investigation contained methylene blue (MB), a model water contaminant, in the absence and presence of iron and copper cations (44.5 mg L −1 copper and 39.2 mg L −1 iron).…”
Section: Resultsmentioning
confidence: 99%
“…They have good stability and are capable of being used as a diagnostic tool in cancer diagnosis and therapy 8. Globally, a lot of research is underway to explore their potential candidacy as drug delivery tool and behavior toward biological systems 914…”
Section: Introductionmentioning
confidence: 99%